Understanding the healthcare professionals’ perspective on the management of diabetic dry skin and the role of urea-based topical application - Sudheer, Anupama; Sen, Dyotona; Jadhwar, Sameer (International Journal of Research in Dermatology, 2024)
Background: Dermatological disorders are common in diabetes mellitus (DM), with xerosis affecting 40% of patients. Xerosis, characterized by scaling and dryness, can lead to complications such as cracks and infections. Urea-based moisturizers are effective in improving skin hydration and barrier function in diabetic patients. Objective was to evaluate the prevalence, awareness, and management of dry skin in diabetic patients and to assess healthcare professionals’ (HCPs) perspectives and patients’ experience with urea-based topical treatments. Methods: This questionnaire-based study involved 363 HCPs (dermatologists and cosmetologists) from India. Data were collected via an 18-question questionnaire in two phases (August and November 2023). The effect of urea-based formulations on diabetic skin dryness was assessed. Results: Data were collected from 1,761 patients with DM, with 96.48% presenting with dry skin. While 48.83% of patients were aware of diabetes-related skin issues, 98.63% of them emphasized the importance of patient education on diabetes-related skin issues. Urea-based moisturizers were prescribed to 97.1% of patients, and 46.29% rated their efficacy as excellent. Most patients reported improvements in dryness and itchiness, with good overall tolerability (46.24%). Conclusions: Urea-based moisturizers are effective and well-tolerated for managing dry skin in diabetic patients. HCPs view urea as essential for maintaining skin hydration and preventing complications associated with xerosis in DM.